Creative social entrepreneurial orientation of traditional woven SMEs - Anggraeni Permatasari; Wawan Dhewanto; Dina Dellyana (President University, 2022)
This study defines entrepreneurial orientation (EO) in traditional woven SMEs in the context of the creative industry. We explore the entrepreneurial process of traditional woven SMEs in Sikka District, Indonesia. This study uses a qualitative method based on grounded research. Data was collected through in-depth interviews and observations. Eight stakeholders participated in this study. Data were analyzed through open, axial, and selective coding to present a systematic approach to new concept development applied by inductive research. The findings define traditional woven SMEs as those determined by creativity and social orientation. This study has limitations in terms of geographic area. Further research is required in this regard. The results can help traditional woven SMEs develop sustainable performance through entrepreneurial orientation. This study leveraged the concept of social entrepreneurship in the context of creative business.